The story of an emerging crisis: the impact of COVID-19 on care home residents with dementia in the UK. (1st November 2021) - Cousins, Emily; de Vries, Kay; Harrison Dening, Karen
Abstract : The impact of COVID-19 in UK care homes has been significant ‐ for staff, residents and people with dementia. Given the rapidly changing circumstances, the media (limitations notwithstanding) have reported vital insights from the front line. A qualitative analysis of news articles across three time points reveals the story of an emerging crisis in UK care homes, beginning with a sole focus on hospital care and resulting in tragically high death rates. This public-facing narrative has potential to: advocate for increased resources in care homes; drive government accountability; highlight improvements for care practices; and bear witness to the experiences of a vulnerable population.